FACTOR STRUCTURE AND RELIABILITY OF THE MALAY VERSION OF THE CHILDHOOD TRAUMA QUESTIONNAIRE- SHORT FORM (M-CTQ-SF) AMONG DRUG ADDICTS IN MALAYSIA - Mey, Loy See (International Journal of Psychosocial Rehabilitation, 2020)
Some studies in the literature have suggested that individuals with drug addiction problem often associated with high prevalence of child abuse and neglect in their life histories. Therefore, the evaluation of childhood maltreatment experiences among the population suffering from drug addiction is essential for the development of effective treatment and psychosocial interventions. The Childhood Trauma Questionnaire (CTQ-SF) is the commonly used measurement for assessing multiple dimensions of childhood traumatic experiences. However, the Malay version of the CTQ-SF (henceforth, M-CTQ-SF) has not been validated among Malaysians with drug abuse problem. In this study, the M-CTQ-SF was administered to 360 drug addicts entering inpatient drug abuse treatment in Malaysia. The construct validity of M-CTQ-SF was examined using a principle component analysis while the reliability was assessed using internal consistency approach (Cronbach alpha method). The result of PCA found a five factor structure with two items cross loaded with two factors. The internal consistency of M-CTQ-SF was adequate except for Physical Neglect and Sexual Abuse reported an unsatisfactory Cronbach alpha (< .70). The study results have suggested that the translated version of M-CTQ-SF can be considered as a valid screening instrument for childhood traumatic experience among population with drug addiction problem.